Improving knowledge of Funiculina quadrangularis and vulnerable marine ecosystems in the south Adriatic - MAČIĆ, VESNA; ĐORĐEVIĆ, NIKOLA; ĐUROVIĆ, MIRKO; PETOVIĆ, SLAVICA; RUSSO, TOMMASO (Mediterranean Marine Science, 2022)
The Adriatic Sea is one of the most exploited areas in the Mediterranean; however, a large part of the South Adriatic Sea remains largely unexplored. Unfortunately, direct and indirect anthropogenic impacts are increasing exponentially, causing a loss of flagship species and threatening ecosystem functioning. This has led to several international conventions demanding better protection and management of sensitive species and areas worldwide. Soft mud facies bearing the sea pen Funiculina quadrangularis are indicators of vulnerable marine ecosystems (VMEs). This study aimed a) to contribute to the knowledge on the distributions of F. quadrangularis and VMEs, and b) to assess the main threats, thus enabling better identification of areas that need protection and ecosystem base management. The results show that F. quadrangularis are distributed from 160 m to 400 m depth, with the highest population density of 0.83 colony/m2 reported in the Adriatic Sea at a 162 m depth. However, using video ground truthing, we registered stresses on deep-sea habitats originating from fishery and marine litter. Further research is needed to ascertain other potentially vulnerable areas. Moreover, international discussion is needed to determine future steps for the protection and sustainable use of resources beyond national jurisdictions.